Pharmacophore modeling and 3D QSAR studies for prediction of matrix metalloproteinases inhibitory activity of hydroxamate derivatives. Issue 1 (January 2017) - Rathee, Dharmender; Lather, Viney; Dureja, Harish
Graphical abstract: Abstract: In order to develop potent inhibitors of matrix metalloproteinase (MMP-2 and MMP-9) as anticancer agents, pharmacophore modeling and three-dimensional quantitative structure–activity relationship (3D-QSAR) models were established using PHASE 3.0. A pharmacophore 5-point (AAARR) model was developed for the studied dataset and the generated model was used to derive the predictive atom-based 3D-QSAR models. After identifying a valid hypothesis, we developed 3D-QSAR models applying the PLS algorithm. The selected 3D-QSAR models were suggestive of the vitality of the electron-withdrawing feature for the MMPs inhibitory potential. In addition, hydrophobic groups, hydrogen bond donor groups, positive ionic and negative ionic features also positively contributed to the MMPs inhibitory potential along with the electron-withdrawing feature. The developed models were statistically robust (MMP-2 Q 2  = 0.51; pred R 2  = 0.67; MMP-9 Q 2  = 0.59; pred R 2  = 0.77). The QSAR results help in identifying a relationship between structural features of hydroxamate derivatives and their activities which could be useful to design newer MMP inhibitors.